1997
DOI: 10.1897/1551-5028(1997)016<2304:jatoda>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Joint Acute Toxicity of Diazinon and Chlorpyrifos to Ceriodaphnia Dubia

Abstract: Abstract-Diazinon and chlorpyrifos are two organophosphorous pesticides widely found in municipal, agricultural, and urban storm water discharges. Because they are often found concurrently, their relationship with respect to joint toxicity is of interest, particularly in regard to interpreting the results of toxicity identification evaluations (TIEs) that point to metabolically activated organophosphorous pesticide(s) as causes of toxicity. Joint toxicity was evaluated using static tests that incorporated 48-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 6 publications
6
60
2
2
Order By: Relevance
“…Additivity has been observed in C. tentans exposed to binary mixtures of the OPs chlorpyrifos, methidation, diazinon, and azinphos methyl [84] and for Ceriodaphnia dubia exposed to the OPs chlorpyrifos and diazinon [85], however, no enzymes measurements were performed in these studies. In contrast, Woods et al [86] observed synergistic effects between chlorpyrifos and profenofos tested on Ceriodaphnia dubia, attributed to an increase in the rate of enzymatic activation of one compound by the other or an inhibition of the enzymes that control detoxification.…”
Section: Mixtures Of Opsmentioning
confidence: 85%
“…Additivity has been observed in C. tentans exposed to binary mixtures of the OPs chlorpyrifos, methidation, diazinon, and azinphos methyl [84] and for Ceriodaphnia dubia exposed to the OPs chlorpyrifos and diazinon [85], however, no enzymes measurements were performed in these studies. In contrast, Woods et al [86] observed synergistic effects between chlorpyrifos and profenofos tested on Ceriodaphnia dubia, attributed to an increase in the rate of enzymatic activation of one compound by the other or an inhibition of the enzymes that control detoxification.…”
Section: Mixtures Of Opsmentioning
confidence: 85%
“…The acute toxicity of diazinon and chlorpyrifos to C. dubia is additive (Bailey et al, 1997). Joint toxicity is estimated from diazinon and chlorpyrifos analytical data by normalizing each concentration to its respective LC 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide pulses have been followed through watersheds, remaining toxic for days from agricultural runoff (Kuivila and Foe, 1995;Werner et al, 2000). Diazinon has been implicated as the primary toxicant in runoff causing acute toxicity to C. dubia, P. promelas, and in situ Corbicula fluminea assays (Bailey et al, 1997;Kuivila and Foe, 1995;Connor, 1995;Waller et al, 1995;Cooke et al, 1995). C. dubia reproduction and growth of C. fluminea in situ closely paralleled the health of the indigenous communities (Dickson et al, 1992;Waller et al, 1995).…”
Section: A General Applicationsmentioning
confidence: 99%
“…In another study, stormwater (from large parking areas surrounding an airport and industry) toxicity was most strongly influenced by cationic metals. Diazinon and chlorpyrifos in urban stromwater showed additive toxicity to C. dubia in a TIE (Bailey et al, 1997). Jirik et al (1998) also used selected phase 1 TIE studies to identify the toxicants most responsible for stormwater toxicity in the Santa Monica Bay area.…”
Section: Toxicity Identification Evaluations (Tie)mentioning
confidence: 99%